Wpływ innowacyjności na konkurencyjność małych i średnich przedsiębiorstw - Wolak-Tuzimek, Anna (The Innovativeness Influence on Small and Medium Sized Enterprises Competitiveness, 2007)
In the Polish economy the innovativeness influence on the enterprise competitiveness is of little importance. Small and medium sized enterprises have a small innovative potential and the researching one is even smaller. Using researching results inserted in PARP reports and in PKPP Lewiatan the author analyzes statistic data concerning a level and structure of innovations at small and medium sized enterprises sector. Moreover, the author points out the elements which may increase the enterprise innovativeness and how they influence the enterprises competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 453-461